Impact of Community-Based Non-communicable Disease Services on the Quality of Life of People Living with HIV in Uganda: A Randomized Controlled Trial - Ddamulira, Christopher; Kiyingi, Frank Pio; Muwanguzi, Eria; Kizza, Stephen S (Disease and Health: Research Developments Vol. 6, 2025)
There was an indication in 2012 that Non Non-communicable diseases (NCDs) were responsible for 38 million (68%) of the world’s 56 million deaths. Almost three-quarters of all NCDs (28 million) and the majority of premature deaths (82%) occur in low and middle-income countries mainly in Asia and Sub-Saharan African (SSA) countries. A comprehensive and culturally applicable community-based Non-Communicable Diseases (NCD) services package was implemented with an aim to test the effectiveness of the community-based NCD services on the Quality of Life (QoL) of people with HIV. The Randomized Controlled Trial (RCT) was conducted to compare the effectiveness of the community-based NCD services as an intervention. The control group received the usual HIV services in the community. Participants were randomly allocated to receive weekly and monthly intervention sessions using the standard care in the community ARV drug distribution points. Paired and independent t-tests were performed to compare changes in the QoL scores at the baseline and the endline. Between November and December 2018, 1076 individuals were screened, of whom 438 were randomly assigned to either the intervention or control group in a ratio of 1:1. The post-intervention results revealed that the community-based NCD services were effective and improved the QoL in all three domains; the physical, environmental and social relationship domains. The study findings further revealed that QoL was higher at the end line across all domains in the treatment group compared to the control group, the mean differences were statistically significant (p = 0.000 < 0.05). Thus, the community-based NCD services were efficacious in improving the QoL of HIV-infected people. Findings could be utilized in regular community service settings for their sustainability and long-term effects. The intervention created an improved understanding of HIV and NCD integration health promotion strategies and community support systems activities by the VHT, ART expert clients and community volunteers. The study recommended that the Government through the Ministry of Health (MOH) review and adopt the transformed community-based HIV and NCD services in the national guidelines for the management of HIV in the communities using the differentiated models.